Fabrication of transparent titanium dioxide thin film at low temperature by sol-gel spin coating method - M. K., Ahmad; N. A., Rasheid; W. S. W., Zaki; A, Zain Ahmed; S, Abdullah; M., Rusop (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.